Transcriptomic analysis identifies enrichment of cAMP/PKA/CREB signaling in invasive lobular breast cancer - Susrutha Puthanmadhom Narayanan; Abdalla M. Wedn; Osama Shiraz Shah; Jian Chen; Daniel D. Brown; Priscilla F. McAuliffe; Steffi Oesterreich; Adrian V. Lee (Breast Cancer Research)
Abstract Objective Invasive lobular breast cancer (ILC) is the most common special type of breast cancer and has unique clinicopathological and molecular hallmarks that differentiate it from the more common invasive carcinoma—no special type (NST). Despite these differences, ILC and NST are treated as a single entity and there is a lack of ILC-targeted therapies. To fill this gap, we sought to identify novel molecular alterations in ILC that could be exploited for targeted therapies. Methods Differential gene expression and Geneset Enrichment and Variation analyses were performed on RNA-seq data from three large public breast cancer databases—the Sweden Cancerome Analysis Network-Breast (SCAN-B; luminal A ILC N = 263, luminal A NST N = 1162), The Cancer Genome Atlas (TCGA; luminal A ILC N = 157, luminal A NST N = 307) and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC; luminal A ILC N = 65, luminal A NST N = 533). Pathways enriched in overlapping differentially expressed genes from these datasets were clustered using Jaccard similarity to identify pathways enriched in ILC. The cAMP/PKA/CREB signaling was studied in ILC, ILC-like and NST cell lines and patient-derived organoids (PDOs) using forskolin, an activator of the pathway. Results Clinicopathological features of patients with ILC and NST in SCAN-B were similar to prior population-based studies. There was a consistent pattern of up-regulation of cAMP/PKA/CREB related signaling in ILC compared to NST in SCAN-B, TCGA and METABRIC. Treatment with forskolin resulted in a greater increase in phospho-CREB in ILC cell lines and organoids than NST. CRISPR deletion of CDH1 in NST cell lines did not alter response of cells to forskolin as measured by phospho-CREB. Forskolin treatment caused growth inhibition in ILC and NST, with ILC cell lines being more sensitive to forskolin-mediated growth inhibition. Conclusion In three separate datasets, cAMP/PKA/CREB signaling was identified to be higher in ILC than NST. This in silico finding was validated in cell line and organoid models. Loss of CDH1 was not sufficient to mediate this phenotype. Future studies should investigate the mechanisms for differential cAMP/PKA/CREB signaling and the potential for therapeutic targeting in patients with ILC. Graphical abstract